Implementation of Government and Business Entity Cooperation in Accelerating Public Works and Public Housing Infrastructure - Moro Asih, Mochamad; Yulianti, Arfiani; Rahulkhan (The International Journal of Education Management and Sociology, 2024)
This study analyzes the Financing of Infrastructure Implementation, Impacts and Problems in Infrastructure Implementation, Proposals, and Recommendations in Infrastructure Implementation in Cooperation between the Government and Business Entities in Accelerating Public Works and Public Housing Infrastructure. The research method uses a descriptive qualitative approach, which describes the phenomena that occur in the research field. The collection technique is through interviews with several informants and ministry staff and field observations to observe things in the area that are by the research focus. Documentation studies include books, archives, and important and official meeting notes. Conclusion Infrastructure development is a priority in Indonesia, as a funding and budget factor from the Ministry of PUPR. Infrastructure development in 2020-2022 will reach IDR 888 trillion. The funding comes from the state expenditure revenue budget and the regional expenditure revenue budget as investment capital in the field of infrastructure. Part of the infrastructure financing is from creative innovation financing through government cooperation schemes and other business entities. It is regulated through Presidential Regulation No. 38 Concerning Cooperation between Government Agencies and Business Entities. The Government's fiscal funding reaches approximately 73%. While funding from state-owned enterprises is about 21%, and from private financing is about 42%.